The Islamisation of psychology: its "why", its "what", its "how", and its "who" - Badri, Malik Babiker (IIUM Press, 2009)
This paper is based on the author's summary of his current book "Out of the lizard's hole" that he wrote as a response to his earlier provocative book 'Dilemma of Muslim Psychologists."